Dissoluble magnesium alloy structure, material and preparation method
By introducing nanocrystals and Cu, Ni, and Co elements that are partially aggregated along the grain boundary in magnesium alloys, the nanoscale primary cell structure is formed, and the plasticity deterioration and high cost of existing soluble magnesium alloy materials are solved, and high strength is achieved Toughness and rapid dissolution effect, suitable for shale oil and gas extraction tools.
Patent Information
- Application Number
- CN202411543850.6
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-10-31
- Publication Date
- 2025-02-07
AI Technical Summary
The existing soluble magnesium alloy materials will deteriorate the plasticity of the material during the alloying process and increase the raw material and processing costs. The high cost of rare earth elements hinders the industrial promotion of high-performance soluble magnesium alloys.
By introducing nanocrystals and Cu, Ni, and Co elements that are partially aggregated along the grain boundary in the magnesium alloy, a nanoscale primary cell structure is formed to improve the mechanical properties and dissolution rate of the material.
It realizes the high strength, toughness and hardness of magnesium alloy materials, and can be quickly dissolved in aqueous chloride ion-containing solutions, meeting the fracturing process needs of shale oil and gas mining tools, while reducing the use of alloying elements and the cost of raw materials.
Smart Images

Figure CN119392062A_ABST
Abstract
Description
Technical Field
[0001] The invention belongs to the technical field of metal materials and processing thereof, and in particular relates to a soluble magnesium alloy structure, material and a preparation method. Background Art
[0002] The information disclosed in this background technology section is only intended to enhance the understanding of the overall background of the invention, and should not necessarily be regarded as an admission or any form of suggestion that the information constitutes the prior art already known to a person skilled in the art.
[0003] The development of soluble metal materials is of great significance to the horizontal staged fracturing process of shale oil and gas. Tools such as bridge plugs and temporary plugging balls made of soluble materials can naturally dissolve in a chloride ion-containing aqueous solution after the fracturing process, avoiding the manual removal process, shortening the mining cycle, and reducing production costs.
[0004] At present, the most widely used soluble metal materials are soluble magnesium alloys, which is due to the low standard electrode potential, high specific strength and specific stiffness of magnesium metal. In order to obtain a rate-controllable dissolution rate and higher strength, the strategy usually adopted is a higher degree of alloying. On the one hand, a certain number of second phases formed inside the microstructure can be rapidly dissolved in a chloride ion-containing aqueous solution through galvanic corrosion with the metal matrix; on the other hand, the strength of the material is improved by the second phase strengthening and solid solution strengthening of the alloy. During the plastic deformation of the metal, dislocations cannot bypass the larger second phases, thus forming dislocation pileups and gradually developing into crack sources for material fracture. Therefore, magnesium alloy materials with a higher degree of alloying tend to deteriorate the plasticity of the material, and a higher degree of alloying will also increase the raw material cost and processing cost of the soluble magnesium alloy.
[0005] According to the Mises criterion, polycrystalline plastic deformation requires five independent slip systems; however, magnesium metal has only two independent slip systems on the basal plane at room temperature, and the critical shear stress of the cylindrical and conical slip systems is relatively high, so the corresponding slip systems are difficult to activate. Tensile twinning can promote coordinated deformation to a certain extent, but the increase is only about 7%. Although the "solution strengthening and plasticization" theory has expanded the strengthening and toughening strategy of magnesium alloys, the high material cost of rare earth elements represented by yttrium has hindered the large-scale industrial promotion of high-performance soluble magnesium alloys.
[0006] With the introduction of the concept of "material materialization", it has become a design idea for new metal materials to greatly improve the comprehensive performance of materials by regulating the defects of different scales (vacancies, dislocations, grain boundaries, etc.) in low-alloyed materials. Summary of the invention
[0007] In view of the above problems, the purpose of the present invention is to provide a soluble magnesium alloy structure, material and preparation method. The present invention obtains a magnesium alloy material with good mechanical properties and solubility by utilizing the structural characteristics of nanocrystals and alloy elements segregated along grain boundaries, which has good application prospects in the field of shale oil and gas development.
[0008] Specifically, the present invention provides the following technical solutions:
[0009] According to a first aspect of the present invention, a soluble magnesium alloy structure is provided, comprising nano-sized magnesium alloy grains and metal elements segregated along grain boundaries; the nano-sized magnesium alloy grains comprise magnesium alloy grains having a size of 1-999 nm; the segregation amount of the metal elements comprises 1-100 atomic layers; and the metal elements are selected from one or more of Cu, Ni, and Co elements.
[0010] The soluble magnesium alloy structure provided by the present invention has good mechanical properties and can be quickly dissolved in a chloride ion-containing aqueous solution. Compared with the micron-scale grain size and the second phase, the nano-scale magnesium alloy grains and the smaller-scale copper, nickel, and cobalt elements segregated along the grain boundaries proposed by the present invention can form a more dense nano-scale primary battery in the chloride ion-containing aqueous solution, thereby accelerating dissolution, wherein the magnesium alloy nanocrystals are the negative electrode and the segregated Cu, Ni, and Co are the positive electrode. In addition, the mechanical properties (hardness, tensile properties, and compression properties) of the magnesium alloy material containing "nanocrystals" and "element grain boundary segregation" are better than those of micron-scale grains.
[0011] In a second aspect of the present invention, there is provided a low alloy material having a soluble magnesium alloy structure, wherein the magnesium alloy is Mg n A a E e The alloy, wherein n, a, and e are the cumulative atomic proportions of elements such as Mg, A, and E, respectively, and n+a+e=100%, and is specifically composed of the following elements in atomic percentage: 0.001at.% to 0.5at.% of A element, 0.001at.% to 0.5at.% of E element, and the balance is Mg element; wherein the A element is selected from one or more of Al, Zn, Ca, Mn, Zr, Si, Sr, and RE elements, and the RE is a rare earth element selected from one or more of Gd, Y, Ce, Nd, Sm, Er, Yb, La, Pr, Pm, Eu, Tb, Dy, Ho, Tm, Lu, and Sc; and the E element is selected from one or more of Cu, Ni, and Co elements.
[0012] Preferably, the soluble magnesium alloy is composed of the following elements in atomic percentage: 0.1 at.% to 0.3 at.% of element A, 0.1 at.% to 0.3 at.% of element E, and the balance being element Mg; wherein element A is selected from one or more of elements Al, Zn, Gd, Y, and Zr; and element E is selected from one or more of elements Cu, Ni, and Co.
[0013] Preferably, the content of the E element is ≥ the total content of the A element.
[0014] The third aspect of the present invention provides a method for preparing the low alloy material according to the second aspect, comprising the following steps:
[0015] S1. Mix various raw materials, melt, refine and cast them in sequence under a protective gas atmosphere to obtain an ingot;
[0016] S2, homogenizing the ingot, extruding the obtained material, and obtaining a soluble magnesium alloy product;
[0017] S3. The soluble magnesium alloy product is processed to obtain nano-sized magnesium alloy grains, which are then heat treated.
[0018] Preferably, in step S1, the raw material is pure Mg (>99.9wt%), pure Al (>99.9wt%), pure Zn (>99.9wt%), Mg-Ca master alloy, Mg-Mn master alloy, Mg-Zr master alloy, Mg-RE master alloy, Mg-Cu master alloy, Mg-Ni master alloy or Mg-Co master alloy.
[0019] Further preferably, in the process of configuring the raw material components, a certain proportion of recycled magnesium alloy can be used to replace the above-mentioned pure metal or intermediate alloy; the certain proportion is 0 to 50% of the total weight of the alloy.
[0020] Preferably, in step S1, the shielding gas is a mixture of CO2 and SF6, and the mixing ratio of CO2 and SF6 is 100-200:1; further preferably, the mixing ratio of CO2 and SF6 in the shielding gas is 150:1.
[0021] Preferably, in step S1, the smelting temperature is 720-760° C., and the smelting time is 40-60 min.
[0022] Preferably, in step S1, the refining time is 20 to 30 minutes.
[0023] Preferably, in step S1, the temperature is raised to 740-780° C. after refining, and then allowed to stand; more preferably, the standing time is 30-40 minutes.
[0024] Preferably, in step S1, during the refining process, the melt is stirred for 5 to 10 minutes.
[0025] Preferably, in step S1, the casting temperature is 680-720°C.
[0026] Preferably, in step S2, the temperature of the homogenization treatment is 500-550° C., and the time is 12-48 hours.
[0027] Preferably, in step S2, the extrusion process is specifically: extrusion forming at a speed of 1.5 to 2.5 m / min; further preferably, the extrusion temperature is 400 to 500° C.; and the extrusion ratio is 5 to 15.
[0028] Preferably, in step S2, the soluble magnesium alloy product is a magnesium alloy rod.
[0029] Preferably, in step S3, the processing method is selected from one or more of shot peening, ultrasonic impact, laser impact, surface mechanical grinding and surface mechanical milling.
[0030] Further preferably, when the processing method is shot peening, the shot peening speed is 60-80 m / s, the shot diameter is 0.5-0.8 mm, and the shot peening time is 5-10 min;
[0031] When the processing method is ultrasonic impact, the static load of the ultrasonic impact is 25-30N, the frequency is 15-20kHz, and the amplitude is 15-20μm.
[0032] Preferably, in step S3, the heat treatment temperature is 100-300° C., and the insulation time is 1-200 h.
[0033] The fourth aspect of the present invention provides the use of the soluble magnesium alloy structure described in the first aspect, the low-alloyed material described in the second aspect and / or the low-alloyed material prepared by the preparation method described in the third aspect in the field of shale oil and gas extraction.
[0034] One or more embodiments of the present invention have at least the following beneficial effects:
[0035] (1) The present invention improves the mechanical properties and dissolution rate of the material by preparing nanocrystals and soluble magnesium alloy structures with Cu, Ni, and Co grain boundary segregation. Nanocrystals can improve the plasticity and toughness of magnesium alloys through grain rotation and grain boundary sliding. Cu, Ni, and Co segregated at the grain boundaries have only a limited atomic layer thickness (can be regarded as atomic clusters, but have not yet formed a second phase), which can regulate the stability of the grain boundaries to improve the hardness and strength of the material; therefore, the alloy prepared by the present invention has high toughness and high hardness, which can meet the characteristic requirements of the fracturing process of shale oil and gas production tools such as temporary plugging balls and bridge plugs. At the same time, Cu, Ni, and Co with a limited atomic layer thickness can form a nanoscale primary battery with magnesium alloy nanocrystals - the former is the positive electrode and the latter is the negative electrode, which can be dissolved relatively quickly in a chloride ion aqueous solution through a discharge reaction, which can meet the requirements for the rapid removal of temporary plugging tools after fracturing.
[0036] (2) The present invention prepares high-performance soluble magnesium alloy materials through a low-alloying method, which reduces the use of alloying elements. A certain amount of recycled materials can also be used to replace pure metals or intermediate alloys (recycling waste magnesium and magnesium alloys can promote resource recycling and the price is relatively low), thereby reducing the cost of raw materials.
[0037] (3) The present invention prepares magnesium alloy fine-grained materials by methods such as melting, homogenization, and plastic deformation, and then obtains nano-grains on the surface of the magnesium alloy product by a surface nano-process. A large number of crystal defects such as vacancies, dislocations, stacking faults, and grain boundaries accumulated during the deformation process can accelerate the diffusion rate of Cu, Ni, and Co, so that the grain boundary segregation of related elements can be achieved by using a lower heat treatment temperature.
[0038] (4) The alloying elements of the present invention do not contain low melting point or toxic elements such as In, Bi, Sn, Hg, Cd, and Pb, which can reduce metal loss or environmental pollution during the smelting process, thereby reducing the cost. The preparation method of the present invention is relatively simple, easy to scale up, and has good application prospects. BRIEF DESCRIPTION OF THE DRAWINGS
[0039] The accompanying drawings in the specification, which constitute a part of the present invention, are used to provide a further understanding of the present invention. The exemplary embodiments of the present invention and their descriptions are used to explain the present invention and do not constitute improper limitations on the present invention.
[0040] Figure 1 The microstructure schematic diagram of the soluble magnesium alloy structure prepared by the present invention, wherein 1 is a nano-grain (1 to 999 nm), and 2 is an element segregated along the grain boundary (1 to 10 atomic layers thick);
[0041] Figure 2 The microstructure morphology of the low alloy material prepared in Example 1 of the present invention;
[0042] Figure 3 This is the microstructural morphology of the low-alloyed material prepared in Comparative Example 1 of the present invention. DETAILED DESCRIPTION
[0043] It should be noted that the following detailed descriptions are illustrative and intended to provide further explanation of the present invention. Unless otherwise specified, all technical and scientific terms used in the present invention have the same meanings as those commonly understood by those skilled in the art to which the present invention belongs.
[0044] As mentioned above, the development of soluble metal materials is of great significance for the horizontal staged fracturing process of shale oil and gas. In order to obtain a controllable dissolution rate and higher strength, the strategy usually adopted is a higher degree of alloying. However, a higher degree of alloying magnesium alloy materials often deteriorates the plasticity of the material, and a higher degree of alloying will also increase the raw material cost and processing cost of the soluble magnesium alloy. Therefore, it has become a design idea for a new type of metal material to greatly improve the comprehensive performance of the material by regulating the defects of different scales (vacancies, dislocations, grain boundaries, etc.) of low-alloyed materials.
[0045] The first typical embodiment of the present invention provides a soluble magnesium alloy structure, which includes nanosized magnesium alloy grains and metal elements segregated along grain boundaries; the nanosized magnesium alloy grains contain magnesium alloy grains with a size of 1-999nm; the segregation amount of the metal elements contains 1-100 atomic layers; the metal elements are selected from one or more of Cu, Ni, and Co elements.
[0046] A second typical embodiment of the present invention provides a low alloy material having a soluble magnesium alloy structure, wherein the magnesium alloy is Mg n A a E e The alloy, wherein n, a, and e are the cumulative atomic proportions of elements such as Mg, A, and E, respectively, and n+a+e=100%, and is specifically composed of the following elements in atomic percentage: 0.001at.% to 0.5at.% of A element, 0.001at.% to 0.5at.% of E element, and the balance is Mg element; wherein the A element is selected from one or more of Al, Zn, Ca, Mn, Zr, Si, Sr, and RE elements, and the RE is a rare earth element selected from one or more of Gd, Y, Ce, Nd, Sm, Er, Yb, La, Pr, Pm, Eu, Tb, Dy, Ho, Tm, Lu, and Sc; and the E element is selected from one or more of Cu, Ni, and Co elements.
[0047] In one or more embodiments of this embodiment, the soluble magnesium alloy is composed of the following elements in atomic percentage: 0.1at.% to 0.3at.% of element A, 0.1at.% to 0.3at.% of element E, and the balance is element Mg; wherein element A is selected from one or more of elements Al, Zn, Gd, Y, and Zr; and element E is selected from one or more of elements Cu, Ni, and Co.
[0048] In one or more examples of this implementation mode, the content of the E element is ≥ the total content of the A element.
[0049] A third typical embodiment of the present invention provides a method for preparing the above-mentioned low-alloyed material, comprising the following steps:
[0050] S1. Mix various raw materials, melt, refine and cast them in sequence under a protective gas atmosphere to obtain an ingot;
[0051] S2, homogenizing the ingot, extruding the obtained material, and obtaining a soluble magnesium alloy product;
[0052] S3. The soluble magnesium alloy product is processed to obtain nano-sized magnesium alloy grains, which are then heat treated.
[0053] In one or more embodiments of this embodiment, in step S1, the raw material is pure Mg (>99.9wt%), pure Al (>99.9wt%), pure Zn (>99.9wt%), Mg-Ca master alloy, Mg-Mn master alloy, Mg-Zr master alloy, Mg-RE master alloy, Mg-Cu master alloy, Mg-Ni master alloy or Mg-Co master alloy.
[0054] In one or more examples of this implementation mode, a certain proportion of recycled magnesium alloy can be used to replace the above-mentioned pure metal or intermediate alloy during the configuration of the raw material components; the certain proportion is 0 to 50% of the total weight of the alloy.
[0055] In one or more examples of this implementation mode, in step S1, the protective gas is a mixture of CO2 and SF6, and the mixing ratio of CO2 and SF6 is 100 to 200:1.
[0056] In one or more examples of this implementation, the mixing ratio of CO2 and SF6 in the protective gas is 150:1.
[0057] In one or more examples of this embodiment, in step S1, the smelting temperature is 720-760° C., and the smelting time is 40-60 min.
[0058] In one or more examples of this implementation mode, in step S1, the refining time is 20 to 30 minutes.
[0059] In one or more examples of this embodiment, in step S1, the temperature is raised to 740-780° C. after refining, and then allowed to stand; more preferably, the standing time is 30-40 minutes.
[0060] In one or more examples of this implementation mode, in step S1, during the refining process, the melt is stirred for 5 to 10 minutes.
[0061] In one or more examples of this embodiment, in step S1, the casting temperature is 680-720°C.
[0062] In one or more examples of this embodiment, in step S2, the temperature of the homogenization treatment is 500-550° C., and the time is 12-48 hours.
[0063] In one or more examples of this implementation mode, in step S2, the extrusion process is specifically: extrusion forming at a speed of 1.5 to 2.5 m / min.
[0064] In one or more examples of this embodiment, the extrusion temperature is 400-500° C.; and the extrusion ratio is 5-15.
[0065] In one or more examples of this implementation mode, in step S2, the soluble magnesium alloy product is a magnesium alloy rod.
[0066] In one or more examples of this embodiment, in step S3, the processing method is selected from one or more of shot peening, ultrasonic impact, laser impact, surface mechanical grinding and surface mechanical milling.
[0067] In one or more examples of this embodiment, when the processing method is shot peening, the shot peening speed is 60 to 80 m / s, the shot diameter is 0.5 to 0.8 mm, and the shot peening time is 5 to 10 min;
[0068] When the processing method is ultrasonic impact, the static load of the ultrasonic impact is 25-30N, the frequency is 15-20kHz, and the amplitude is 15-20μm.
[0069] In one or more examples of this embodiment, in step S3, the heat treatment temperature is 100 to 300° C., and the insulation time is 1 to 200 hours.
[0070] A fourth typical embodiment of the present invention provides application of the above-mentioned soluble magnesium alloy structure and / or the above-mentioned low-alloyed material in the field of shale oil and gas extraction.
[0071] The soluble magnesium alloy provided by the present invention is added with Cu, Ni and Co elements and segregated at the grain boundaries as the positive electrode of galvanic corrosion; the magnesium alloy matrix is used as the negative electrode of galvanic corrosion, and a large number of nanometer-scale primary cells formed by the two can react and dissolve quickly in water with chloride ion aqueous solution as electrolyte.
[0072] Adding elements such as Al, Zn, Ca, Mn, Si, Sr, Zr and RE to the soluble magnesium alloy provided by the present invention can improve the casting and hot forming properties of the material. Among them, Al and Si can improve the casting properties of the magnesium alloy; Al, Zn and RE can enhance the strength of the magnesium alloy matrix through solid solution strengthening; Ca, Mn, Sr, Zr and RE can refine the cast structure of the magnesium alloy.
[0073] The present invention will be further described in detail below in conjunction with specific embodiments. It should be noted that the specific embodiments are intended to explain the present invention rather than to limit it.
[0074] Example 1 : This embodiment provides a low-alloyed material that can dissolve magnesium alloy structure and a preparation method thereof.
[0075] A low alloy material capable of dissolving a magnesium alloy structure comprises a Mg-Al-Zn-Cu-Ni alloy and is composed of the following elements in atomic percentages: 0.19 at.% Al, 0.1 at.% Zn, 0.2 at.% Cu, 0.1 at.% Ni, and the remainder being Mg element.
[0076] A method for preparing the low alloy material of this embodiment comprises the following steps:
[0077] (1) According to the above alloy element ratio, pure Mg, pure Al, pure Zn, Mg-Cu master alloy, and Mg-Ni master alloy are weighed; under the protection of CO2+SF6 mixed gas (volume ratio of 150:1), pure Mg is melted at 740°C, and then pure Al, pure Zn, Mg-Cu master alloy, and Mg-Ni master alloy are added in sequence; at 740°C, the temperature is kept for 40 minutes, stirred for 5 minutes, and refined for 20 minutes. After refining, the temperature is raised to 780°C and allowed to stand for 30 minutes, and then cast at 700°C to form a soluble magnesium alloy ingot.
[0078] (2) The ingot is kept at 500°C for 24 hours and air-cooled; then the ingot is processed into an extrusion billet; and the ingot is extruded into a soluble magnesium alloy rod using an extrusion machine at an extrusion temperature of 450°C, an extrusion ratio of 10, and an extrusion speed of 2 m / min.
[0079] (3) A nano-sized grain structure is formed on the surface of the magnesium alloy rod by shot peening, wherein the shot peening speed is 80 m / s, the shot diameter is 0.8 mm, and the shot peening time is 10 min.
[0080] (4) The magnesium alloy rod prepared in step (3) is subjected to heat treatment, specifically: heat preservation at 150° C. for 20 h.
[0081] Example 2 : This embodiment provides a low-alloyed material that can dissolve magnesium alloy structure and a preparation method thereof.
[0082] A low alloy material capable of dissolving a magnesium alloy structure comprises a Mg-Gd-Y-Cu-Ni alloy and is composed of the following elements in atomic percentage: 0.15 at.% of Gd, 0.1 at.% of Y, 0.2 at.% of Cu, 0.1 at.% of Ni, and the rest being Mg element.
[0083] A method for preparing the low alloy material of this embodiment comprises the following steps:
[0084] (1) According to the above alloy element ratio, pure Mg, Mg-Gd master alloy, Mg-Y master alloy, Mg-Cu master alloy and Mg-Ni master alloy are weighed; under the protection of CO2+SF6 mixed gas (volume ratio of 150:1), pure Mg is melted at 750°C, and then Mg-Gd master alloy, Mg-Y master alloy, Mg-Cu master alloy and Mg-Ni master alloy are added in sequence; at 750°C, the temperature is kept for 40 minutes, stirred for 5 minutes, and refined for 20 minutes. After refining, the temperature is raised to 780°C and allowed to stand for 30 minutes, and then cast at 700°C to form a soluble magnesium alloy ingot.
[0085] (2) The ingot is kept at 510°C for 24 hours and air-cooled; then the ingot is processed into an extrusion billet; and the ingot is extruded into a soluble magnesium alloy rod using an extrusion machine at an extrusion temperature of 450°C, an extrusion ratio of 10, and an extrusion speed of 2 m / min.
[0086] (3) A nano-sized grain structure is formed on the surface of the magnesium alloy rod by shot peening, wherein the shot peening speed is 70 m / s, the shot diameter is 0.8 mm, and the shot peening time is 5 min.
[0087] (4) The magnesium alloy rod prepared in step (3) is subjected to heat treatment, specifically: heat preservation at 140° C. for 24 hours.
[0088] Example 3 : This embodiment provides a low-alloyed material that can dissolve magnesium alloy structure and a preparation method thereof.
[0089] A low alloy material capable of dissolving magnesium alloy structure is a Mg-Zn-Zr-Cu-Co alloy composed of the following elements in atomic percentage: Zn 0.12 at.%, Zr 0.1% Cu 0.2 at.%, Co 0.1 at.%, and the rest being Mg element.
[0090] A method for preparing the low alloy material of this embodiment comprises the following steps:
[0091] (1) According to the above alloy element ratio, pure Mg, pure Zn, Mg-Zr master alloy, Mg-Cu master alloy and Mg-Ni master alloy are weighed; under the protection of CO2+SF6 mixed gas (volume ratio of 100:1), pure Mg is melted at 740°C, and then pure Zn, Mg-Zr master alloy, Mg-Cu master alloy and Mg-Co master alloy are added in sequence; at 740°C, the temperature is kept for 40 minutes, stirred for 5 minutes, and refined for 20 minutes. After refining, the temperature is raised to 760°C and allowed to stand for 30 minutes, and then cast at 700°C to form a soluble magnesium alloy ingot.
[0092] (2) The ingot is kept at 500°C for 16 hours and air-cooled; then the ingot is processed into an extrusion billet; and the ingot is extruded into a soluble magnesium alloy rod using an extrusion machine at an extrusion temperature of 440°C, an extrusion ratio of 8, and an extrusion speed of 1.5 m / min.
[0093] (3) A nano-sized grain structure is formed on the surface of the magnesium alloy rod by ultrasonic impact, wherein the static load of the ultrasonic impact is 30N, the frequency is 20kHz, and the amplitude is 20μm.
[0094] (4) The magnesium alloy rod prepared in step (3) is subjected to heat treatment, specifically: heat preservation at 140° C. for 24 hours.
[0095] Example 4 : This embodiment provides a low-alloyed material that can dissolve magnesium alloy structure and a preparation method thereof.
[0096] A low alloy material capable of dissolving a magnesium alloy structure comprises a Mg-Al-Zn-Cu-Ni alloy composed of the following elements in atomic percentage: 0.3 at.% Al, 0.1 at.% Zn, 0.3 at.% Cu, 0.1 at.% Ni, and the rest being Mg element.
[0097] A method for preparing the low alloy material of this embodiment comprises the following steps:
[0098] (1) According to the above alloy element ratio, pure Mg, AZ31 recycled material (10wt.%), pure Al, pure Zn, Mg-Cu master alloy, and Mg-Ni master alloy are weighed; under the protection of CO2+SF6 mixed gas (volume ratio of 150:1), pure Mg is melted at 740°C, and then pure Al, pure Zn, Mg-Cu master alloy, and Mg-Ni master alloy are added in sequence; at 740°C, the temperature is kept for 40 minutes, stirred for 5 minutes, and refined for 20 minutes. After refining, the temperature is raised to 780°C and allowed to stand for 30 minutes, and then cast at 700°C to form a soluble magnesium alloy ingot.
[0099] (2) The ingot is kept at 500°C for 24 hours and air-cooled; then the ingot is processed into an extrusion billet; and the ingot is extruded into a soluble magnesium alloy rod using an extrusion machine at an extrusion temperature of 450°C, an extrusion ratio of 10, and an extrusion speed of 2 m / min.
[0100] (3) A nano-sized grain structure is formed on the surface of the magnesium alloy rod by shot peening, wherein the shot peening speed is 80 m / s, the shot diameter is 0.8 mm, and the shot peening time is 10 min.
[0101] (4) The magnesium alloy rod prepared in step (3) is subjected to heat treatment, specifically: heat preservation at 150° C. for 20 h.
[0102] Comparative Example 1 :
[0103] The difference from Example 1 is that: in the preparation process of this comparative example, no surface nano-processing is performed (the operation of step (3) is not performed), and the specific components involved and other preparation processes are the same as those of Example 1.
[0104] Comparative Example 2 :
[0105] The difference from Example 1 is that in the preparation process of this comparative example, no heat treatment is performed after the surface nano-crystallization (the operation of step (4) is not performed), and the specific components involved and other preparation processes are the same as those of Example 1.
[0106] Comparative Example 3 :
[0107] The difference from Example 1 is that the heat treatment process in step (4) of the preparation process of this comparative example is: keeping warm at 400°C for 24 hours, and the specific components involved and other preparation processes are the same as those in Example 1.
[0108] Comparative Example 4 :
[0109] The difference from Example 1 is that: this comparative example does not perform surface nano-treatment, and the heat treatment process of step (4) is: keeping warm at 400°C for 24 hours, and the specific components involved and other preparation processes are the same as those in Example 1.
[0110] Comparative Example 5 :
[0111] The difference from Example 1 is that the low-alloyed material prepared in this comparative example is a Mg-Al-Zn-Cu-Ni alloy composed of the following elements in atomic percentage: Al 3.0at.%, Zn 1.0at.%, Cu0.2at.%, Ni0.1at.%, and the rest is Mg element; the specific preparation process is the same as that in Example 1.
[0112] Comparative Example 6 :
[0113] The difference from Example 1 is that the low-alloyed material prepared in this comparative example is a Mg-Al-Zn-Cu-Ni alloy composed of the following elements in atomic percentage: Al 0.19at.%, Zn 0.1at.%, Cu2.0at.%, Ni1.0at.%, and the rest is Mg element; the specific preparation process is the same as that in Example 1.
[0114] Comparative Example 7 :
[0115] The difference from Example 1 is that the low alloy material of this comparative example is a Mg-Al-Zn alloy composed of the following elements in atomic percentage: Al 0.19 at.%, Zn 0.1 at.%, and the rest being Mg element.
[0116] Test Example 1 :
[0117] This test example tests the mechanical properties and solubility properties of the alloys of Examples 1 to 4 and Comparative Examples 1 to 7, as shown in Table 1. The room temperature tensile property test method is in accordance with GB T 228.1-2010; the Vickers hardness is in accordance with GB / T4340.1-2024; and the solubility property is tested at 93°C and 3% KCl aqueous solution.
[0118] Table 1 Mechanical properties and dissolution rate of magnesium alloy at room temperature
[0119]
[0120] As can be seen from Table 1, the low alloyed materials with soluble magnesium alloy structure prepared in Examples 1 to 4 of the present invention have the advantages of low alloying (<1at.%), high elongation (>15%), good strength (tensile strength>350MPa) / Vickers hardness (>190HV) / dissolution rate (>80), etc. This is the result of the combined effect of nano-scale grains and element segregation (schematic diagram as shown in the figure). Figure 1 The microstructure image is shown in Figure 2 As shown in the figure, the prepared material has higher mechanical properties and dissolution rate, and can meet the performance requirements of temporary plugging tools such as fracturing balls and bridge plugs.
[0121] Among them, a certain proportion of recycled materials was used in the alloy melting and casting process of Example 4, and the relevant performance was not significantly reduced compared with Examples 1 to 3, indicating that the soluble metal structure of the present invention has a wide adaptability to alloy components.
[0122] Comparative Examples 1 to 3 did not adopt the surface nano-crystallization preparation method and / or alloy element segregation heat treatment process set in Examples 1 to 4 of the present invention, and the relevant properties were significantly reduced, indicating that the structure proposed in the present invention has a decisive influence on the mechanical properties and solubility properties.
[0123] Among them, the comparative example 1 was not subjected to surface nano-treatment, and thus no nano-grain structure was formed (microstructure image as shown in FIG. Figure 3 As shown). Since the microstructure is micron-scale grains, although the same heat treatment as in the embodiment is performed to produce element segregation, a certain amount of Mg (Cu, Ni) phase is inevitably formed-the dispersion of Cu and Ni elements is not enough, and the strengthening effect and dissolution rate are greatly reduced; Comparative Example 2 is not heat-treated after surface nano-treatment, and Comparative Example 3 is heat-treated at a higher temperature after surface nano-treatment, which respectively affects the alloy element segregation and grain size structure, so the performance is also significantly reduced; Comparative Example 4 is also not subjected to surface nano-treatment, and only element segregation is controlled by heat treatment. Although the dissolution rate is slightly improved, the mechanical properties are deteriorated.
[0124] In the materials of Comparative Examples 5 to 6, the Al / Zn and Cu / Ni element contents were increased respectively, which resulted in a significant increase in the second phase in the organization, affecting the alloy element segregation process, thereby resulting in a reduction in the dissolution rate and mechanical properties of the material to the same extent.
[0125] The alloy composition of Comparative Example 7 does not contain Cu and Ni elements, so there is no segregation of the corresponding elements, and the corresponding mechanical properties and dissolution rate are significantly reduced.
[0126] In summary, the present invention discloses a soluble magnesium alloy structure, material and preparation method, which have good mechanical properties and solubility properties and can meet the demand for soluble magnesium alloy components required for shale oil and gas development.
[0127] The above description is only a preferred embodiment of the present invention and is not intended to limit the present invention. For those skilled in the art, the present invention may have various modifications and variations. Any modification, equivalent replacement, improvement, etc. made within the spirit and principle of the present invention shall be included in the protection scope of the present invention.
Claims
1. A dissolvable magnesium alloy structure, characterized in that: The magnesium alloy structure includes nano-sized magnesium alloy grains and metal elements segregated along grain boundaries; the nano-sized magnesium alloy grains include magnesium alloy grains with a size of 1-999nm; the segregation amount of the metal elements includes 1-100 atomic layers; the metal elements are selected from one or more of Cu, Ni, and Co elements.
2. A low alloy material capable of dissolving a magnesium alloy structure as claimed in claim 1, characterized in that: The magnesium alloy is Mg n A a E e The alloy, wherein n, a, and e are the cumulative atomic proportions of elements such as Mg, A, and E, respectively, and n+a+e=100%, and is specifically composed of the following elements in atomic percentage: 0.001at.% to 0.5at.% of A element, 0.001at.% to 0.5at.% of E element, and the balance is Mg element; wherein the A element is selected from one or more of Al, Zn, Ca, Mn, Zr, Si, Sr, and RE elements, and the RE is a rare earth element selected from one or more of Gd, Y, Ce, Nd, Sm, Er, Yb, La, Pr, Pm, Eu, Tb, Dy, Ho, Tm, Lu, and Sc; and the E element is selected from one or more of Cu, Ni, and Co elements.
3. The low alloy material according to claim 2, characterized in that: The soluble magnesium alloy is composed of the following elements in atomic percentage: 0.1 at.% to 0.3 at.% of element A, 0.1 at.% to 0.3 at.% of element E, and the balance is element Mg; wherein element A is selected from one or more of elements Al, Zn, Gd, Y, and Zr; and element E is selected from one or more of elements Cu, Ni, and Co.
4. The low alloy material according to claim 3, characterized in that: The content of the E element is ≥ the total content of the A elements.
5. A method for preparing the low alloy material according to any one of claims 2 to 4, characterized in that: The following steps are involved: S1. Mix various raw materials, melt, refine and cast them in sequence under a protective gas atmosphere to obtain an ingot; S2, homogenizing the ingot, extruding the obtained material, and obtaining a soluble magnesium alloy product; S3. The soluble magnesium alloy product is processed to obtain nano-sized magnesium alloy grains, which are then heat treated.
6. The preparation method according to claim 5, characterized in that: In step S1, the raw material is pure Mg, pure Al, pure Zn, Mg-Ca master alloy, Mg-Mn master alloy, Mg-Zr master alloy, Mg-RE master alloy, Mg-Cu master alloy, Mg-Ni master alloy or Mg-Co master alloy; Preferably, in the process of configuring the raw material composition, a certain proportion of recycled magnesium alloy can be used to replace the above-mentioned pure metal or intermediate alloy; the certain proportion is 0 to 50% of the total weight of the alloy.
7. The preparation method according to claim 5, characterized in that: In step S1, the protective gas is a mixture of CO2 and SF6, and the mixing ratio of CO2 and SF6 is 100-200:1; preferably, the mixing ratio of CO2 and SF6 in the protective gas is 150:1; Preferably, the smelting temperature is 720-760°C and the smelting time is 40-60 minutes; Preferably, the refining time is 20 to 30 minutes; Preferably, after the refining, the temperature is raised to 740-780°C and then allowed to stand; further preferably, the standing time is 30-40 minutes; Preferably, during the refining process, the melt is stirred for 5 to 10 minutes; Preferably, the casting temperature is 680-720°C.
8. The preparation method according to claim 5, characterized in that: In step S2, the temperature of the homogenization treatment is 500-550°C and the time is 12-48 hours; Preferably, the extrusion process is specifically: extrusion forming at a speed of 1.5 to 2.5 m / min; further preferably, the extrusion temperature is 400 to 500° C.; the extrusion ratio is 5 to 15; Preferably, the soluble magnesium alloy product is a magnesium alloy rod.
9. The preparation method according to claim 5, characterized in that: In step S3, the processing method is selected from one or more of shot peening, ultrasonic impact, laser impact, surface mechanical grinding and surface mechanical milling; Preferably, when the processing method is shot peening, the shot peening speed is 60-80 m / s, the shot diameter is 0.5-0.8 mm, and the shot peening time is 5-10 min; When the processing method is ultrasonic impact, the static load of the ultrasonic impact is 25-30N, the frequency is 15-20kHz, and the amplitude is 15-20μm; The heat treatment temperature is 100-300° C., and the heat preservation time is 1-200 hours.
10. Use of the soluble magnesium alloy structure according to claim 1, the low alloyed material according to any one of claims 2 to 4, and / or the low alloyed material prepared by the preparation method according to any one of claims 5 to 9 in the field of shale oil and gas production.
Citation Information
Cited By
Soluble magnesium alloy material and preparation method thereof
CN120425213A